2020
DOI: 10.1002/ppsc.202000265
|View full text |Cite
|
Sign up to set email alerts
|

Facile Preparation and Excellent Ultraviolet Shielding Application of Polyurethane‐TiO2 Composite Microcapsules

Abstract: In this work, butyl stearate, isophorone diisocyanate, and glycerol are used to prepare reticulated polyurethane microcapsules using interfacial polymerization. In addition, anatase nano‐TiO2 is added to prepare TiO2‐polyurethane phase change microcapsules during the polymerization process. Polarized light microscope, scanning electron microscope, Fourier‐transform infrared spectroscopy, thermogravimetric, differential scanning calorimeter, and other methods demonstrate the successful preparation of microcapsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…For this purpose, we use KH-550 coupling agent to modify the surface of hydrophilic nano titanium dioxide, improving the aggregation and dispersion of titanium dioxide nanotubes in the insulation paint matrix. Then, the modified titanium dioxide nanotubes are compounded with flame retardant insulation paint, and it is expected that the compounded flame retardant system can prepare flame retardant insulation paint with good comprehensive performance with low addition amount [2,3]. Therefore, this study aims to incorporate titanium dioxide into the insulation paint, which can be filled into the defects of polymers to improve the flame retardancy, toughness, thermal stability, corrosion resistance, and wear resistance of the insulation paint [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, we use KH-550 coupling agent to modify the surface of hydrophilic nano titanium dioxide, improving the aggregation and dispersion of titanium dioxide nanotubes in the insulation paint matrix. Then, the modified titanium dioxide nanotubes are compounded with flame retardant insulation paint, and it is expected that the compounded flame retardant system can prepare flame retardant insulation paint with good comprehensive performance with low addition amount [2,3]. Therefore, this study aims to incorporate titanium dioxide into the insulation paint, which can be filled into the defects of polymers to improve the flame retardancy, toughness, thermal stability, corrosion resistance, and wear resistance of the insulation paint [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Yin et al selected tetraethyl orthosilicate (TEOS) as functional shell-forming monomers to enhance the thermal stability and compactness of traditional polyurea MicroPCMs [ 25 ], and the result indicated that the smoothness and compactness of both polyuria-SiO 2 and polyurethane-SiO 2 microcapsules was enhanced slightly when compared with that without TEOS. Hong et al [ 26 ] prepared polyurethane-TiO 2 microcapsules through interfacial polymerization, and the result indicated that the addition of TiO 2 enhances the thermal stability and mechanical strength of the prepared composite microcapsules. Therefore, the preparation of composite shell microcapsules has become a research hotspot and point of focus in recent years.…”
Section: Introductionmentioning
confidence: 99%